Centrifugation facilitates incorporation of fibrin in poly(lactic-co-glycolic acid) scaffold - Mohamad, Mohd Yusof; Md Nazir, Noorhidayah; Abdul Rahman, Rozlin; Mohamad Sukri, Norhamiza; Ahmad Radzi, Muhammad Aa'zamuddin; Sha'ban, Munirah (2014)
INTRODUCTION: The incorporation of fibrin onto synthetic poly (lactic-co-glycolic acid) or PLGA scaffold allows efficient cell attachment, proliferation, differentiation and migration. The study aimed to compare between direct pipetting and centrifugation techniques for the incorporation of fibrin onto PLGA. MATERIALS AND METHODS: Poly lactic-co-glycolic acid is fabricated via solvent casting, salt leaching technique. Sieved sodium chloride (NaCl) particles (approx.400μm) were dispersed in a polymer/solvent solution (0.2% w/v PLGA/methylene chloride). The mixture was casted into cylindrical disk scaffold using silicone moulds (7 mm in diameter and 3 mm in thickness). The scaffolds were immersed in deionized water for 48 hours to leach out NaCl and then, freeze-dried. Fibrin was derived from the whole blood via centrifugation at 4800 rpm, 5minutes, 4°C. The resulting supernatant was filter-sterilized and stored at -20°C until use. Direct pipetting method involves pipetting approx. 100 µl of fibrin on the surface of PLGA. Centrifugation method involved dipping of PLGA scaffold in 1 ml of fibrin and centrifugation at 5600 rpm for 10 minutes. Both scaffolds for each method were polymerized by dropping calcium chloride solution. The scaffolds were stored at room temperature and analysed using scanning electron microscopy. RESULTS AND DISCUSSION: The results indicated that the centrifugation shows better fibrin incorporation inside the PLGA pores when compared to the direct pipetting method. CONCLUSION: This easy centrifugation procedure may facilitate the establishment of efficient cell delivery system for tissue engineering.